Studying the uranium pollution in reduction the levels of the C-Peptide and Vitamin D for healthy and diabetic patients in Najaf City Iraq - Razzaq, Doaa Falah; Saleh, Dhuha S.; Al-Mashhadani, Asia H. (AIP conference proceedings, 2020)
A total of 88 diabetic patients and control healthy subjects was involved in the present study in Najaf city. Uranium concentration level was estimated using CR-39 detector method in all subjected which has been grouped in four groups of 22 individuals each (22 healthy controls; 22 diabetic patients taken from different regions and 22 healthy controls; 22 diabetic patients taken from Al-Ansaar region in Najaf city Iraq). In atrial to find the relation and association between uranium pollution in urine samples and increase of diabetes cases in Najaf city. The levels of biological parameters C- Peptide and Vitamin D was estimated in sera of all subject using ELISA technique as they are important biological parameters in the set of diabetes mellitis cases. Result indicate the presence of uranium pollution in 100% urine samples. No significant difference was found between values of G-1, G-2, G-3 and G-4 but it was found with mean value of G-1 having the greater value from all groups. The mean value of Vitamin D indicates the presence of Vitamin D deficiency in all subject, also C-Peptide value was low when compared with normal value. There was no significant difference among the mean values of all groups. Our conclusion is presence of uranium pollution as a main factor in the set and increased DM cases through triggering an autoimmune reaction which result in Vitamin D deficiency and insulin deficiency with final result of increased number of diabetes mellitis patients in Najaf city.